Реконструктивні трансформації забудови історичного центру малого міста (на прикладі площі пам’яті в місті бар вінницької області) - Лещенко, Н. А.; Leshchenko, N. (Видавництво Львівської політехніки, 2018)
Проаналізовано реконструктивні трансформації, які відбулися із забудовою ринкової площі малого історичного міста, що призвело до втрати нею її історичної функції, але водночас отримання нових, не менш важливих функцій. Показано, як це вплинуло на сучасне планування та забудову площі. Визначено стратегію ревалоризації як необхідної реконструктивної трансформації для її активізації. Надано рекомендації, як розвинути її наявні сучасні функції, відновити історичну і гармонічно їх поєднати для створення якісного міського публічного простору.

The buildings and planing of the historical small towns always feel different qualitative changes in the process of their existence and development. It can be planned or chaotic. The results of these changes can improve the quality of architecture, urban environment and life in it, or, vice versa, can lead to its degradation and destruction. Very often, the disappearance of the historical buildings or the appearance of only one the new building are changing the functionality of the whole square. If it's planned, the changes are expected. And if the calculations are the correct, they usually lead to the better quality of the resulting architectural urban environment. In the case of chaotic changes, whether accidental or deliberately made, the urban architectural environment usually has a loss. They often become the cause of its functional depletion or disturbance and lead to the decrease in its activity and to its degradation, as a result, in the first case, or to the violation of its integrity and intimacy, in the event of the appearance of an undesirable function, in the second case. Such qualitative changes are felt especially clearly in the historical environment of small towns. Let's consider them on the example of the former Market square, and the Memory square now in Bar, Vinnytsia region. The reconstructive transformations, that took place with this square in the twentieth century, led to the partial loss of its historical market function. But, at the same time, it received the new functions, memorial and recreation, not less important. The town park was organized in the center of the former Market square. It’s unordered right now. There are no elements of improvement in it. And, in spite of the fact that it has many old trees, it performs the transit function instead of traditional recreational function. People walk through it only to cross the square, but don’t come specifically to spend their free time. This space is not quite popular among the locals. How to change it? So, the strategy of its revalorisation is determined as a necessary reconstructive transformation for its activization. Also, the recommendations are given on how to develop its existing modern functions and how to restore its historical function and harmoniously combine them to create high-quality urban public space. The strategy of increasing the value of the existing urban historical environment is: - to activate it through the organization as the multifunctional urban space, where the existing and historical functions are harmoniously combined; - to attract local residents and tourists to the square and park by creating the comfortable urban space for staying and interesting for visiting and spending free time; - to create the shopping arcade which will restore and organize the traditional historical function of the market square that currently exists in the form of spontaneous trade “from cars”; - to enter the new building into the existing situation as correctly as possible. It can be modern architecture, but it must be coordinated with the existing surrounding buildings in scale, storeys, forms, material of facade decoration, color; - to create the pedestrian zone on the territory of the square, extending the existing pedestrian zone of the Bona Sforzi street and of the St. Nicholas street. The updated square has to delicately combine the restored historical market function (the new shopping arcade), the activated existing recreational function (the ordered existing park with landscaping elements, places for communication and recreation) and the supplemented memorial function (the new memorial complex of the ATO heroes). And this should be done so that the last function will be used not only on the official holidays, and people will come to this place in any of their free time. The square should be transformed from the transit and almost “empty” territory into the multifunctional friendly space. So, the concept of the square updating is to create the interesting, comfortable public space for the people of all ages and preferences, which will harmoniously combine the existing and the new buildings, located around it. The general composition and new pedestrian directions are based on the already existing most popular directions of the movement that unite the territory of the Memory square with the existing monuments of local and national architecture: the Holy Assumption Church, the St. Anna's Church, the complex of the buildings of the Pokrovsky Monastery and the remains of the Bar Fortress and provide their species disclosure. Thus, the overall strategy for the revalorisation of the Memory Square are the harmonious combination of the contextual historical and new architecture, the activation of the existing historical environment through its functional filling to create a coherent, qualitative, comfortable and interesting urban environment where the person is the main one. This will restore the regional traditions, will preserve the identity of the small town, will attract the tourists’ attention to it, will raise the social and architectural value of the urban environment, that will contribute to its sustainable development and will improve the living standards of local residents.
Reconstructive transformations of the small town’s historical center (on the example of the memory square in bar, vinnytsia region)
Keywords: ревалоризація; історичний центр малого міста; ринкова площа; площа Пам’яті; якісний міський публічний простір; revalorisation; small town historical center; market square; Memory square; high- quality urban public space; 72.025.4/5